Dynamic Responses of Barley Root Succinyl-Proteome to Short-Term Phosphate Starvation and Recovery - Wang, Juncheng; Ma, Zengke; Li, Chengdao; Ren, Panrong; Yao, Lirong; Li, Baochun; Meng, Yaxiong; Ma, Xiaole; Si, Erjing; Yang, Ke; Shang, Xunwu; Wang, Huajun (Frontiers in Plant Science, 2021)
Barley (Hordeum vulgare L.)—a major cereal crop—has low Pi demand, which is a distinct advantage for studying the tolerance mechanisms of phosphorus deficiency. We surveyed dynamic protein succinylation events in barley roots in response to and recovery from Pi starvation by firstly evaluating the impact of Pi starvation in a Pi-tolerant (GN121) and Pi-sensitive (GN42) barley genotype exposed to long-term low Pi (40 d) followed by a high-Pi recovery for 10 d. An integrated proteomics approach involving label-free, immune-affinity enrichment, and high-resolution LC-MS/MS spectrometric analysis was then used to quantify succinylome and proteome in GN121 roots under short-term Pi starvation (6, 48 h) and Pi recovery (6, 48 h). We identified 2,840 succinylation sites (Ksuc) across 884 proteins; of which, 11 representative Ksuc motifs had the preferred amino acid residue (lysine). Furthermore, there were 81 differentially abundant succinylated proteins (DFASPs) from 119 succinylated sites, 83 DFASPs from 110 succinylated sites, 93 DFASPs from 139 succinylated sites, and 91 DFASPs from 123 succinylated sites during Pi starvation for 6 and 48 h and during Pi recovery for 6 and 48 h, respectively. Pi starvation enriched ribosome pathways, glycolysis, and RNA degradation. Pi recovery enriched the TCA cycle, glycolysis, and oxidative phosphorylation. Importantly, many of the DFASPs identified during Pi starvation were significantly overexpressed during Pi recovery. These results suggest that barley roots can regulate specific Ksuc site changes in response to Pi stress as well as specific metabolic processes. Resolving the metabolic pathways of succinylated protein regulation characteristics will improve phosphate acquisition and utilization efficiency in crops.